The association between body mass index class and coronavirus disease 2019 outcomes - Al-Salameh, Abdallah (Int J Obes (Lond), 2020)
BACKGROUND/OBJECTIVES: A growing body of data suggests that obesity influences coronavirus disease 2019 (COVID-19). Our study’s primary objective was to assess the association between body mass index (BMI) categories and critical forms of COVID-19. SUBJECTS/METHODS: Data on consecutive adult patients hospitalized with laboratory-confirmed COVID-19 at Amiens University Hospital (Amiens, France) were extracted retrospectively. The association between BMI categories and the composite primary endpoint (admission to the intensive care unit or death) was probed in a logistic regression analysis. RESULTS: In total, 433 patients were included, and BMI data were available for 329: 20 were underweight (6.1%), 95 have a normal weight (28.9%), 90 were overweight (27.4%), and 124 were obese (37.7%). The BMI category was associated with the primary endpoint in the fully adjusted model; the odds ratio (OR) [95% confidence interval (CI)] for overweight and obesity were respectively 1.58 [0.77–3.24] and 2.58 [1.28–5.31]. The ORs [95% CI] for ICU admission were similar for overweight (3.16 [1.29–8.06]) and obesity (3.05 [1.25–7.82]) in the fully adjusted model. The unadjusted ORs for death were similar in all BMI categories while obesity only was associated with higher risk after adjustment. CONCLUSIONS: Our results suggest that overweight (and not only obesity) is associated with ICU admission, but overweight is not associated with death.